Penerapan Penerapan kompres hangat terhadap penurunan dismenore pada remaja putri - Apriani, Dwi; Andriyanti, Septi (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2022)
Background: Dysmenorrhea is abdominal pain that comes from uterine cramps that occur during menstruation. Pain occurs at the same time as the onset of menstruation and lasts several hours to several days until it reaches the peak of pain. A warm compress can be done by adolescent women at home as an alternative to reduce pain due to dysmenorrhea. Purpose: to determine the application of warm compresses to decrease dysmenorrhea in adolescent girls. The approach used by researchers in this study is a qualitative approach, where the results are not in the form of numbers. The samples used were two patients who experienced menstrual pain. Method: observation and assessment of patients on Nn'A' and Nn'D' who experience dysmenorrhea, before and after being given warm compress therapy. Results: this study indicate that after being given the application of a warm compress, the pain scale in case I Nn